STUDY OF CHEMICAL COMPOUNDS AND ANTIBACTERIAL ACTIVITY OF KEFA FOREST HONEY STORED AT DIFFERENT TIMES AGAINST THE BACTERIA AEROMONAS HYDROPILLA AND VIBRIO ALGINOLITYCUS - Salosso, Yuliana; Rahma, Andi Taufika; Senjata, Aris Ndena; Djonu, Asriati (Jurnal Perikanan Unram, 2024)
This research aims to determine the stability of the chemical compound content and antibacterial activity of kefa forest honey stored at different times, against the bacteria Aeromonas hydropilla and Vibrio alginolitycus which are pathogenic bacteria in fish farming. Tests for the chemical compound content of honey include testing for alkaloid compounds using the Culvenor-Fiztgerald method, saponins using the foam test, terpenes and steroids using the Lieberman-Burchard method, tannins using the addition of FeCl3 while flavonoids using the addition of HCl and Mg powder reagents. The total sugar content was measured using a spectrophotometer, the water content was measured using the gravimetric method and the pH using a pH meter. The antibacterial activity of honey was tested using the disc method without dilution. The research results showed that kefa forest honey taken at different times showed the same active compound content or did not change. The longer it is stored, the sugar, water and pH content of forest honey from Kefa decreases, but the decrease is not too big. Forest honey from Kefa, both new and stored for 6 months and 1 year, still has antibacterial activity against the bacteria A. hydropilla and V. alginolitycus.